Sexual dysfunction: Prevalence and relationship with depression and other socio-demographic factors among the type II diabetic women of Pakistan - Rubab Gul; Sana Gul; Muhammad Azmat Khan; Raja Rizwan Ul Haq Satti (Journal of the Pakistan Medical Association, 2021)
Objective: To find out the association between sexual dysfunction and depressive symptoms among the type II diabetic women of Pakistan. Methods: Study was conducted at Military hospital RWP from November 2017 to October 2018Two hundred and fiftydiabeticwomen reporting for the routine follow-upat a tertiary care hospital in Rawalpindi Pakistan were approached to participate in our study. Female sexual function index (FSFI) was used to assess the sexual function of the women who participated in our study. Presence of depressive symptoms was assessed by using the Beck depressive inventory II (BDI-II). Relationship of age, duration of diabetes, depression, education, level of family income and type of treatment (insulin or oral hypoglycemic)was assessed with the sexual dysfunction when regression analysis was applied. Results: Out of 250 diabetic women, who were administered FSFI, 35.6% had no sexual problem while 64.5% had significant dysfunction regarding their sexuality. 71.6% of the patients had presence of depressive symptoms while 28.4% were negative on screening of depression with BDI-II. Increasing age and presence of depressive symptoms had considerable association with the sexual dysfunction. Conclusion: High prevalence of sexual dysfunction was recorded among diabetic women of our part of the world. Women with psychological problems should be paid special attention in this regard.Female diabetic patients with increasing ageshould also be screened regularly for psycho-sexual problems during the course of treatment of DM. Keywords: sexual dysfunction; DM; FSFI; depressive symptoms Continuous...